Control Strategies for Retrial Queues with a Single Retrial Attempt - Pryshchepa, Oksana; Komada , Paweł (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
In this paper, we consider retrial queueing systems with an input flow rate that depends on the number of calls in an orbit and with a limited number of retrials. According to threshold and hysteresis strategies, optimization problems for the effective operation of the system are formulated and solved. The quality functionals are built in terms of the stationary probabilities of the underlying Markov process describing the system. By solving the optimization problems, we obtain optimal policies that ensure effective and stable system operation under varying load conditions and retrial limitations.